Application of Government Internal Control System (SPIP) in Implementation of Income and Expenditure Buget (APBD) to Improve Quality of Financial Report of Local Government of Pangkajene and Islands Regency (Pangkep) - Alfiyah Agussalim; Fadillah Amin; Nila Firdausi Nuzula (Sekolah Pascasarjana Universitas Brawijaya, 2018)
Background of this research is implementation of regional autonomy which gives broad authority to regions to manage of their own regions, including financial management. To managing local financial needed transparency and accountability and to realize it takes the control and Government Internal Control System (SPIP). Internal control plays a role overseeing government activities at the implementation of the budget and also to improve the quality of local government financial report.The purpose of this research to analyze application of Government Internal Control System in Implementation of APBD to improve quality of financial report of local government of Pangkep regency. This research uses descriptive research method with qualitative approach. Result of this research is application of SPIP in Pangkep Regency is adjusted with Annual Supervision Work Program (PKPT) Inspectorate of Pangkep Regency that determined by regent. In application of supervision activity, the surveillance apparatus ofÂ governmentâ€™s internal (APIP) began to review at planning phase that budget activity plan ofÂ regional work unit (RKA-SKPD) review as a quality assurance in order to produce a quality APBD. SPIP is important to improve the quality of financial report because APIP oversees the financial management that will impact on the quality of financial report. In the application of SPIP in Pangkep Regency there are some factors internal and external that support and obstacles.